Investigating Factors Affecting English Language Engagement among the Law Department Learners in Papua: An Empirical Analysis” - Roida Hutabalian; Tenri Ugi Irianto; Markus Deli Girik Allo (Universitas Cokroaminoto Palopo, 2023)
The objective of the study is to investigate the factors affecting English Language Engagement among the Law Department Learners in Papua. This study is qualitative by implementing a cross-sectional design to capture a snapshot of English language engagement among the Law Department Learners in Papua. A diverse sample of the Law Department Learners in Papua from multiple schools had been selected. The sample included learners from different grades, socio-economic backgrounds, and language proficiency levels in the Law Department Learners in Papua. Qualitative data from open-ended questions were subjected to thematic analysis to identify recurring patterns and themes related to intrinsic and extrinsic factors. This study confirms that conventional monotony in instructional materials and insufficient reading practice are the main factors that make the Law Department Learners in Papua lazy to learn English in the classroom. It is recommended to delve deeper into the identified factors of conventional monotony in instructional materials and insufficient reading practice as contributors to students' lack of motivation in learning English in the classroom.